Prank dan Gimmik dalam Perspektif Hadis - Ainun Nabilah; Muhammad Alif; Salim Rosyadi (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
In this article we discuss Pranks and Gimmicks from a Hadith Perspective. The issue of pranks and gimmicks has now become commonplace and often occurs in the public domain. Hadith is the second source of law after the Al-Qur'an and as a proposition containing ethical norms is also a relevant reference for addressing this issue. Therefore, this article aims to discuss the issue of pranks and gimmicks from a hadith perspective and how to apply the hadith in carrying out pranks and gimmicks. Pranks and gimmicks can be done as long as they promote the truth without causing anything negative to society and the people around them and vice versa. Which is explained from the Hadith which contains the Prophet Muhammad SAW's prohibition regarding the action of taking something even if the aim is to joke by lying. This research uses library research. By studying books, writings, reading books and journals and rivieuw literature from other references. As well as collecting hadiths related to the object being studied. This research aims to open up the public's perspective regarding prank and gimmicks trends so that people can review the principles of the Koran and Hadith. Pranks and gimmicks may be carried out on condition that they prioritize the principles of truth and do not harm the people around them.